SEDIMENTOLOGICAL AND GEOCHEMICAL ANALYSIS OF MIOCENE DEPOSITS IN MOSCHOPOTAMOS AREA, IN THE WESTERN PART OF AXIOS-THERMAIKOS BASIN, NW GREECE - Savva, V.; Tserolas, P.; Maravelis, A.; Bourli, N.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2016)
A total of 27 samples of the Moschopotamos area lignite-bearing strata were studied in regard of their geochemical and sedimentary characteristics. Organic content and calcium carbonate evaluation, sieve analysis and micropaleontological observations were used and combined to investigate the paleoenvironment and the depositional conditions of the study area. TOC analysis showed that organic matter values range from 0.07% up to 13.42% with an average of ~3.26 %. The high average of organic carbon content indicates a promising basis for the sediments’ source rock potential, inquiring further and thorough examination. CaCO3 measurements present a range between 4% and 23%. A comparison between TOC-CaCO3 content throughout the stratigraphic column presented certain synchronous and inverse trends, due to alterations of the depositional conditions. This study provides new insights for the understanding of the broader Axios-Thermaikos basin, and depositional conditions in the North Aegean area.